2021
DOI: 10.1098/rspb.2020.3143
|View full text |Cite
|
Sign up to set email alerts
|

Species-area and network-area relationships in host–helminth interactions

Abstract: The scaling relationship observed between species richness and the geographical area sampled (i.e. the species-area relationship (SAR)) is a widely recognized macroecological relationship. Recently, this theory has been extended to trophic interactions, suggesting that geographical area may influence the structure of species interaction networks (i.e. network-area relationships (NARs)). Here, we use a global dataset of host–helminth parasite interactions to test existing predictions from macroecological theory… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 42 publications
3
8
0
1
Order By: Relevance
“…Specifically, network size, total links, average degree, relative modularity, and the number of keystone OTUs were all significantly higher on larger islands. These results are consistent with studies of food webs and mutualism networks of macro-organisms 5,6,26,29 . For instance, Galiana et al found that the complexity (network size, links, and links per species) of food webs scaled positively with area in both theoretical simulations and empirical observations 4,6 .…”
Section: Impact Statementsupporting
confidence: 92%
“…Specifically, network size, total links, average degree, relative modularity, and the number of keystone OTUs were all significantly higher on larger islands. These results are consistent with studies of food webs and mutualism networks of macro-organisms 5,6,26,29 . For instance, Galiana et al found that the complexity (network size, links, and links per species) of food webs scaled positively with area in both theoretical simulations and empirical observations 4,6 .…”
Section: Impact Statementsupporting
confidence: 92%
“…Here, we analyse how networks vary in several properties simultaneously (Pinheiro et al, 2019; Thébault & Fontaine, 2010), without rescaling nestedness and modularity using null models that are based on the other network properties (Dallas & Jordano, 2021; Felix et al, 2022). This decision follows from the understanding that ecological and evolutionary processes shape interaction networks as a whole and that, by combining properties, we may achieve deeper insights into these processes (Guimarães, 2020; Segar et al, 2020).…”
Section: Methodsmentioning
confidence: 99%
“…This is an inherent limitation, one which must be considered as how host–helminth associations change across the coarsely defined geographical range of host and parasite species. However, these data represent a herculean effort to compile, curate and distribute > 250,000 host–helminth associations distributed around the world (Gibson et al., 2005), creating opportunities to explore macroecological patterns in host–parasite associations (Dallas et al., 2018, 2019; Dallas & Becker, 2021; Dallas & Jordano, 2021b; Dallas & Poisot, 2018). Efforts are being made to aggregate and curate species interaction network data from individual studies at finer spatial scales (e.g., Poisot et al.…”
Section: Methodsmentioning
confidence: 99%
“…However, these data represent a herculean effort to compile, curate and distribute > 250,000 host-helminth associations distributed around the world (Gibson et al, 2005), creating opportunities to explore macroecological patterns in host-parasite associations (Dallas et al, , 2019Dallas & Becker, 2021;Dallas & Jordano, 2021b;Dallas & Poisot, 2018). Efforts are being made to aggregate and curate species interaction network data from individual studies at finer spatial scales (e.g., Poisot et al (2016)), but even these collections suffer from some of the same geographical coverage biases present in the host-helminth association data used here (Poisot et al, 2021).…”
Section: Host-helminth Interaction Datamentioning
confidence: 99%
See 1 more Smart Citation